16. WHAT VISUAL PERCEPTUAL ANOMALIES CAN TELL US ABOUT SCHIZOPHRENIA: NEURAL MECHANISMS AND THEIR DIAGNOSTIC SPECIFICITY. (9th April 2019) - Sponheim, Scott
Abstract: A quarter of patients with schizophrenia endorse visual hallucinations while two-thirds report subtle perceptual anomalies of visual experience. Yet, little is known about the origin of these visual disturbances and their significance to the disorder. Does schizophrenia represent a unique class of perceptual anomalies or do common mechanisms affect other disorders? Understanding the nature of this defining feature of schizophrenia could help elucidate etiology and address whether visual perceptual phenomena should be considered diagnostic. This symposium will present new findings from four independent laboratories regarding the nature and diagnostic specificity of visual disturbances in schizophrenia. Brian Keane will present results demonstrating visual shape completion deficits in first-episode and chronic schizophrenia patients (d>.8; p<10–6). The deficits are maximally present by the first psychotic break; linked to cognitive disorganization and poor premorbid functioning; reduced in bipolar disorder; and not explicable by medication use, poor orientation discrimination, or impoverished attention/motivation. At the same time, patients exhibit normal sensitivity to the illusory contour boundaries that compose the discriminated shapes, indicating that dysfunctional visual shape completion stems from a lessened ability to notice and use illusory contours at a conceptual stage of analysis. Scott Sponheim will present findings of early visual cortical abnormalities in schizophrenia. Analysis of MEG and functional MRI data reveal that schizophrenia is associated with basic perceptual abnormalities during initial sensory registration of a stimulus, while aberrant use of perceptual context occurs later across visual cortex. Data from biological relatives of people with schizophrenia and bipolar affective disorder patients indicate that early visual cortical anomalies do not mark unexpressed genetic liability for schizophrenia and are generally not shared with bipolar affective disorder. Jason Johannesen will present on the perception of animacy in visual motion. Individuals with schizophrenia have difficulty deriving causal inferences from social scenes, whether portrayed by human actors or simple geometric shapes. In the latter case, when reliant only on object motion, performance is reliable using different stimuli, related to affect recognition and Theory of Mind, and distinguishes schizophrenia from non-psychotic samples with higher accuracy than IQ or visual attention to still images. Ivy Tso will examine the high-level function of gaze perception. Using psychophysical methods, two cognitive processes underlying gaze perception (visual perceptual sensitivity, self-referential bias) are isolated, and patients with schizophrenia and bipolar disorder show abnormalities in both. Dynamic causal modeling of fMRI data demonstrates three characteristics of neural dynamics during gaze perception in schizophrenia: reduced visual cortical response to sensory input; weakened feedforward connectivity from the visual cortex; and aberrant increase of top-down suppression of visual cortex when analyzing gaze direction (vs. gender) of face stimuli. These findings suggest impaired visual processing and potentially compensatory reliance on higher-level functions (e.g., beliefs) contribute to altered social cognition in psychosis. Sohee Park will serve as discussant and speak to how the diverse set of visual disturbances in schizophrenia informs our understanding of the disorder.